2018
DOI: 10.3168/jds.2017-13247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding unlimited amounts of milk replacer for the first 5 weeks of age on rumen and small intestinal growth and development in dairy calves

Abstract: The development of the gastrointestinal tract in newborn calves is essential for sufficient nutrient uptake. An intensive milk feeding during the neonatal period may impair the rumen development in calves. The aim of this study was to investigate effects of milk replacer (MR) feeding in unlimited amounts for the first 5 wk of age on the gastrointestinal growth and development in preruminant calves at wk 9 of age. Twenty-eight newborn Holstein and Holstein × Charolais crossbred calves (19 male and 9 female) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 44 publications
(89 reference statements)
5
40
0
3
Order By: Relevance
“…Farmers mainly based weaning decisions on calf age, with some also considering calf bodyweight or starter intake, recognising that calves should be consuming over 1 kg/day of dry calf starter before weaning to indicate sufficient rumen development and prevent growth checks [1]. These practices should support gastrointestinal growth and development in dairy calves [65]. However, not all farmers provided calves with access to water from birth, which may negatively affect rumen development, restricting pre-weaning feed-efficiency and impeding growth both pre-and post-weaning [30].…”
Section: Discussionmentioning
confidence: 99%
“…Farmers mainly based weaning decisions on calf age, with some also considering calf bodyweight or starter intake, recognising that calves should be consuming over 1 kg/day of dry calf starter before weaning to indicate sufficient rumen development and prevent growth checks [1]. These practices should support gastrointestinal growth and development in dairy calves [65]. However, not all farmers provided calves with access to water from birth, which may negatively affect rumen development, restricting pre-weaning feed-efficiency and impeding growth both pre-and post-weaning [30].…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that intake of solid feed and weight gain increased during weaning in calves fed elevated amounts of milk and weaned through the step-down method compared with those fed milk conventionally. More recent studies (Schäff et al, 2016(Schäff et al, , 2018 have also used the "step-down" method by feeding MR (125 g of MR powder per L) ad libitum for 5 wk, followed by reduction in MR proportionally day by day to 6 L of MR at wk 7 compared with calves fed only 6 L until weaning to investigate growth, metabolic adaptation, health, and rumen and small intestinal growth. The benefits reported in this study were greater perirenal fat and muscle mass and increased anabolic metabolism (as indicated by increased insulin-like growth factor 1 concentration in blood) for step-down calves compared with those who had restricted amounts of milk.…”
Section: Weaning Strategiesmentioning
confidence: 99%
“…Boito et al 2015atribuíram esse efeito ao valor biológico do sucedâneo, que é menor que o do leite integral e apresenta uma menor taxa de absorção dos nutrientes quando comparados ao leite integral. Além de atributos nutricionais influenciarem no ganho de peso dos animais, outro fator determinante diz respeito às características organolépticas dos substitutos lácteos, o que dificulta a adaptação dos animais a essa dieta (França et al, 2011;Schäff et al, 2018).…”
Section: Resultsunclassified
“…Isso se deve ao fato de existirem diversas marcas de sucedâneo no comércio e com diferentes composições. Quando o substituto lácteo não comporta os níveis nutricionais adequados e não é utilizado corretamente, pode acarretar alguns problemas nutricionais e digestivos tendo como destaque: excesso de amido e de fibra, tipo e inadequada incorporação da gordura e utilização de fontes proteicas de baixo aproveitamento ou que provocam transtornos digestivos nos bezerros, além de deterioração gradual na integridade das vilosidades intestinais, em consequência de reações alérgicas (Schäff et al, 2018).…”
Section: Introductionunclassified